Women’s issues: Upward mobility through adult education - Jane Lee; Glenna Williams; Katie Barwick-Snell; Elizabeth Hayes; Bob Nolan (Adult Education Research Conference, 1995)
This paper addresses the issue of access and opportunity for women to advance both educationally and economically in work and profession settings through non-formal education exemplified by mentorships and non credit programming, and through formal education as exemplified by non-traditional students in higher education. The approaches to these issues will be through three separate theoretical perspectives. One perspective derives from Darkenwald, Scanlan, Valentine and Hayes who studied deterrents to participation. Another perspective derives from Rice’s work on the access of welfare women to higher education. A final perspective comes from Riley and Wrench who assert that women, in general, are denied the opportunity for mentoring relationships so often given to men in the workplace. Hence the papers address the upward mobility of women in the workplace, in rural communities and in higher education.